ANALYSING DESTINATION IMAGE FROM A CONSUMER BEHAVIOUR PERSPECTIVE - Baptista, Nuno; Matos, Nelson (Journal of Tourism, Sustainability and Well-being, 2018)
Trough a narrative literature review, this article frames the evolution of destination image within the evolution of destination branding. Main theories used, methodologies, relevant findings and implications to marketing practice are identified. Four relevant conclusions are extracted: first, recent studies of destination image research tend to adopt a joint cognitiveaffective approach in an attempt to capture destination image in a more effective way; second, the dimensions of destination image (overall image, affective image and cognitive image) affect consumer satisfaction and consumer loyalty differently; third, the current academic perspective on destination branding is mostly based on the notion that destination image is not susceptible of being easily changed by marketing efforts. Finally, residents, as privileged interpreters of place image should be called to participate in branding efforts.